Marginalised groups in india : historiography, politics, and policies - Debnath, Kunal; Chatterjee, Souvik (New York : Routledge, 2024)
"This book intersects marginality, politics, and policies by focusing on the narratives of selective marginalised groups within India. Encouraging inclusive government policies that considers the diverse identities of individuals and groups within India, this book is a systematic documentation of the lived experiences of various marginalised collectives, such as the Naths of Bengal, the De-notified Tribes of Maharashtra, the Kukis of Manipur, and the Beggars. The chapters use historiography as a method to understand narratives of marginality in India, illuminating how power imbalances in Indian society lead to the marginalisation of specific groups, depriving them of fundamental rights and opportunities, while others enjoy privileges. The political analysis of this edited volume introspects the political dynamics that perpetuate marginalisation. It details the aspirations of various marginal groups in evolving and changing socio-political circumstances. The book offers a deeper understanding of the intricate issues faced by marginalised groups. It will be of interest to students, academicians, and researchers in South Asian Studies, Subaltern Studies, Political Science, Sociology, Social History, and Migration/refugee studies"--
1. Introduction: The Axes of MarginalitySection A: Caste and Ethnicity through the Lens of Marginality2. Sunk in Oblivion: The Marginalisation and Resistance of the Naths of Bengal;3. Living In and Out of Marginality: Observing 'Dehasadhana' Among the Matuas Through the Prism of 'Sahajiya' Tradition of Dissent;4. Citizenship and Denizenship: The Chakma Community's Dilemma in Arunachal Pradesh;5. Competing Perspectives of Ethno-nationalisms in Contemporary India: The Marginalised Kukis and Making Sense of the Recent Ethnic Conflict in ManipurSection B: Gender Marginalisation6. The Socio-economic Marginalisation of Dalit Women in India: A Critical Overview;7. Unveiling Marginalisation: Neuroqueer Experiences at the Intersection of Neurodivergence and Gender/Sexual Diversity in India;8. Relative Marginalisation and Limited Access of Women to Healthcare Services: A Case Study of West Bengal;9. Marginalisation of Space: The Strategic Arrangements of Domestic Sphere and the Neoliberal City in IndiaSection C: States and Vulnerability10. Marginalisation and Vulnerability of Workers in Tea Gardens in North Bengal;11. Locating the Bengali Bubbles: Language, Ethnicity, and Assam's Federal Conundrum;12. Urban Margins and Nomadic Marginalities: Elucidating the Status of Habitation among Pardhis of MumbaiSection D: Public Policies and the Marginal Communities13. E-Governance: A Critical Appraisal of Digital Tools to Mitigate Marginalisation;14. Empowering Women and Revitalising Rural Communities: Exploring the Socio-Economic Consequences of Bihar's JEEViKA Program;15. Beggars and Policy Discourse: Searching for a Solution of an Age-old Marginality;16. Concluding Remarks: Marginality in the Indian Scenario;Index
Keywords: Marginality, Social -- Political aspects -- India; Caste -- Political aspects -- India; Caste-based discrimination -- India; Dalit women -- India -- Social conditions; Social isolation -- India; Marginality, Social -- Religious aspects -- Hinduism